DURATION OF PRONE POSITIONING AFTER MACULAR HOLE SURGERY DETERMINED BY SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY. Issue 8 (August 2017) - Sano, Masahiko; Inoue, Makoto; Itoh, Yuji; Kita, Yoshiyuki; Hirota, Kazunari; Koto, Takashi; Hirakata, Akito
Abstract : Purpose: To compare the closure rate of macular hole closure and duration of the prone positioning after macular hole (MH) surgery with two protocols for halting the prone positioning. Methods: The authors studied 129 eyes of 125 consecutive patients with MH who had undergone vitrectomy. In 60 eyes of 59 patients, the prone positioning was halted after detecting an MH closure in the swept-source optical coherence tomographic images (SS group). In 69 eyes of 66 patients, the prone position was halted by the surgeon's decision (conventional group). The MH closure rate and duration of the prone positioning were compared. Results: Clear images of the MH were recorded in the SS group on postoperative Day 1 in 58 eyes (97%). In the SS group, MH closure was detected on postoperative Day 1 in 47 eyes (78%) and Day 2 in 4 eyes (7%). The MH was closed in 58 eyes (97%) in the SS group and 69 eyes (100%) in the conventional group ( P = 0.21). None of the eyes had a reopening of the MH. The duration of prone positioning in the SS group was 1.8 ± 2.5 days, which was significantly shorter than that in the conventional group at 8.4 ± 4.2 days ( P < 0.0001). Conclusion: The SS-OCT protocol can significantly decrease the duration of the prone positioning without a reopening of the MH. Abstract : The halting of prone positioning after macular hole surgery by monitoring the closure by swept-source optical coherence tomography can decrease the duration of the prone positioning with identical macular hole closure rates and visual outcome compared with the conventional decision of prone positioning by the surgeons.